581 Impact of Weight on Insomnia Severity, Sleep Quality, and Insomnia Improvement in a Clinically Referred Pediatric Sample. (3rd May 2021) - Duraccio, Kara; Graef, Danielle; Beebe, Dean; Byars, Kelly
Abstract: Introduction: Children with overweight/obesity are more likely to have shortened sleep, though little is known about the role of weight status in insomnia severity, sleep quality, and sleep hygiene in clinically referred youth. Methods: A total of 1133 children (43.7% female) presented to a Pediatric Behavioral Sleep Medicine Clinic for insomnia. At the initial evaluation, caregivers of children ages 2–10.9 years (N = 744) completed the Pediatric Insomnia Severity Scale (PISI) and the Children's Sleep Habits Questionnaire (CSHQ); adolescents ages 11–18 years (N = 389) completed the PISI, the Adolescent Sleep Hygiene Scale (ASHS), and the Adolescent Sleep Wake Scale (ASWS). The PISI was completed during at least one Pediatric Behavioral Sleep Medicine visit subsequent to evaluation and initiation of treatment. Patient height and weight, objectively measured within 3 months of the initial evaluation, was used to determine sex-adjusted body mass index z-scores (BMIz). Hierarchal linear regression models were used to determine the impact of BMIz on baseline PISI insomnia severity scores, and CSHQ, ASHS, and ASWS total scores, after covarying for income. Repeated-measures general linear modeling was used to determine whether weight status moderated improvement in insomnia severity over time, covarying for income. Results: For children (ages 2–10.9), weight was not associated with baseline insomnia severity (p=.62) or predictive of insomnia improvement following behavioral sleep medicine intervention (p=.71), though higher weight predicted poorer parent-reported sleep quality (p=.006). For adolescents (ages 11–18), higher weight was predictive of higher baseline insomnia severity (p=.026), though did not predict insomnia improvement over time (p = .86); higher weight was also predictive of poorer sleep hygiene (p<.001) and worse sleep quality (p=.03). Conclusion: Initial insomnia severity and subjective sleep quality may be worse for youth of higher weight, particularly for adolescents; these findings increase our understanding of how and when overweight/obesity negatively impacts sleep. Fortunately, youth with higher weight respond equally well to pediatric behavioral sleep medicine interventions as their lower-weight peers, suggesting that these interventions need not be modified based on patient weight. Support (if any): Cincinnati Children's Hospital Medical Center Division of Behavioral Medicine and Clinical Psychology's Research Funds